Early life factors associated with growth and cognitive development of infants at 24 months in Seremban, Malaysia - Abdul Razak, Nurliyana (2021)
The first 2 years of life is an important period for growth and development. Exposure to adverse environment may have long-term effects on health and cognitive performance. This cohort study aimed to determine the association between early life factors with growth and cognitive development of infants at 24 months of age. A total of 117 mother-infant pairs were followed-up from 6 to 24 months. Socio-demographic background (parents’ age, ethnicity, educational attainment, occupation, household income, infant’s gestational age, date of birth, sex) was obtained using a questionnaire. Mother’s information during pregnancy (weight and height at booking, history of gestational diabetes mellitus, gravida, weight at each antenatal visit) was obtained from patient card. Pre-pregnancy BMI and gestational weight gain were calculated. Habitual food intakes during pregnancy was assessed using a semi-quantitative food frequency questionnaire and dietary patterns were constructed using principal component factor analysis. Maternal intelligence was assessed using Raven’s Standard Progressive Matrices. Post-natal depression was assessed using Edinburgh Postnatal Depression Scale (EPDS) at 6 months, infant temperament using Revised Infant Behaviour Questionnaire (IBQ-R) and home environment quality was assessed using Infant Toddler HOME Inventory (IT-HOME) at 12 months. Mothers were interviewed on infant feeding practices, including milk and complementary feeding. Infant’s dietary intakes at 6-24 months were obtained through 24-hour dietary recall interview with mothers, and dietary diversity at 12-24 months based on indicators for assessing Infant and Young Child Feeding (IYCF) practices, were determined. Anthropometric measurements (weight and length) were conducted at 6-24 months, and weight-for-age (WAZ), length-for-age (LAZ), and weight-for-length (WLZ) status were determined. Cognitive development was assessed using Bayley-III at 6-24 months. P-trend for growth from birth to 24 months and cognitive development from 6 to 24 months were analysed using repeated measures ANOVA for continuous variables and chi-square test for linear-by-linear association for categorical variables. Individual Growth Curve (IGC) modelling was conducted using Linear Mixed Methods to determine the longitudinal growth trajectory from birth to 24 months and cognitive development trajectory from 6 to 24 months. Univariate logistic regression analysis was conducted to determine factors associated with growth status (underweight, stunting, overweight/obesity) at 24 months and was used as selection criteria (p<.25) for inclusion of variables in the multivariate logistic regression analysis. Different variables were adjusted for different factors (e.g., for pre-natal factors and underweight, data were adjusted for monthly household income, infant’s sex and gestational age, for nutrient intakes and underweight, data were adjusted for monthly household income, infant’s sex and total energy intake). Univariate linear regression was conducted to determine factors associated with cognitive development at 24 months and was used as selection criteria (p<.25) for inclusion of variables in the multivariate linear regression analysis. Different variables were adjusted for different factors (e.g., for socio-demographic factors, data were adjusted for infant’s birth weight, for pre-natal factors, data were adjusted for mother’s educational level, infant’s sex and birth weight). Significance level was determined at p<.05. There were 53.0% boys and 47.0% girls. The mean gestational age was 38.68 weeks (SD=1.14) and the prevalence of low birth weight (LBW) was 7.7%. A linear decreasing trend was observed in the WAZ (p-trend<.01) and LAZ (p-trend<.01). For WLZ, an increasing trend was observed (p-trend<.01), from birth to 24 months. The prevalence of underweight, stunting, wasting, and overweight/obesity at 24 months was 15.4%, 17.1%, 5.1% and 9.4%, respectively. There was also a linear increase in cognitive development from 6 to 24 months, although at 12 months the increment was small and the mean cognitive composite score was lower than at any other ages. The prevalence of cognitive delay at 24 months was 6.8%. Being underweight at 6, 12, and 18 months were associated with higher risk of underweight at 24 months. Higher birth weight, Adj OR=0.13, 95%CI [0.02, 0.92], and higher intake of iron at 18 months, Adj OR=0.80, 95%CI [0.64, 0.99], were associated with lower risk for underweight at 24 months. Conversely, being LBW increases the risk of underweight at 24 months, as using categorical data did not change the findings. There was no significant association between socio-demographic factors, other pre-natal factors (e.g., maternal height, birth length) and post-natal factors (e.g., maternal postnatal depression, maternal intelligence, infant temperament, home environment quality and other nutrients) with underweight at 24 months. Higher maternal height, Adj OR=0.01, 95%CI [0.01, 0.16], and longer birth length, Adj OR=0.72, 95%CI [0.53, 0.98], were associated with lower risk for stunting at 24 months. Being stunted at 6, 12, and 18 months, were associated with higher risk for stunting at 24 months. There was no significant association between socio-demographic factors, other pre-natal factors (e.g., GWG), and post-natal factors (e.g., maternal postnatal depression, maternal intelligence, infant temperament, exclusive breastfeeding duration, dietary diversity and nutrient intakes) with stunting at 24 months. Higher dietary diversity score at 24 months, Adj OR=1.78, 95%CI [1.03, 3.07], and being overweight/obese at 6, 12, and 18 months, were associated with higher risk for being overweight/obese at 24 months. There was no significant association between socio-demographic factors, pre-natal factors (e.g., maternal pre-pregnancy BMI, dietary pattern during pregnancy) and other post-natal factors (e.g., maternal intelligence, home environment quality and nutrient intakes) with overweight/obesity at 24 months. Sex, father’s years of education, maternal intelligence, home environment quality, WAZ status at 12 and 18 months, LAZ status at 24 months, and cognitive composite score at 6-18 months, were found to be significant predictors of cognitive development at 24 months (p<.05). There was no significant association between monthly household income, pre-pregnancy BMI, dietary pattern during pregnancy, dietary diversity, and nutrient intakes, with cognitive development at 24 months. Therefore, ensuring proper growth and provision of cognitively stimulating home environment are important in the first 2 years of life.